PENGARUH PEMBERIAN TEH HIJAU TERHADAP KADAR KOLESTEROL PADA WANITA MENOPAUSE - Bela Purnama Dewi; Venny Mayumi; Marlisa (Jurnal Kesehatan dan Pembangunan, 2024)
Based on data from the World Health Organization (WHO), in 2021, hypercholesterolemia was recorded in more than 160 million people in the world with total cholesterol levels > 200 mg/dl, which is in the quite high category and more than 34 million American adults had total cholesterol levels > 240 mg/dl which is high and requires therapy. Non-pharmacological treatment can be done with herbal medicine or what is known as herbal medicine, namely treatment using herbal medicines including green tea. The aim of this research was to determine the effect of giving green tea on cholesterol levels in menopausal women. This research method uses a pre-experiment design with a one group pre-post test design. The sample in this study was 47 menopausal women with high cholesterol levels, using a purposive sampling technique. The results of the research showed that the value of cholesterol levels after the intervention of giving green tea to menopausal women was 0.001 < 0.05. It can be concluded that there was an effect of giving green tea on reducing cholesterol levels in menopausal women. Green tea is a beverage ingredient that is well known to the public and is very easy to find and the price is relatively cheap. Knowledge about the antioxidant effects of green tea on reducing cholesterol levels is also very useful because it can be an alternative medicine that is safe for health. This is very well known because hypercholesterolemia is still a health problem that is often found in the world.